Pengaruh Kesejahteraan Guru Terhadap Kinerja Guru SD Muhammadiyah PK Kottabarat dan SD Muhammadiyah 10 Tipes - Salma Nur Hasanah; Almuntaqo Zainuddin (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Teacher welfare is one of the problems in the education sector that occurs in Indonesia. The level of teacher welfare in Indonesia is very worrying where honorary teachers only get IDR 150,000 – IDR 700,000/month, there are several private schools demanding their rights for four months starting from January-April which have not been paid by the agency where they work, work environment problems, comfort, organizational climate, and others. The aim of this research is to determine the influence of teacher welfare on teacher performance at SD Muhammadiyah PK Kottabarat and SD Muhammadiyah 10 Types. This research uses a correlational descriptive quantitative research type. The research subjects were 31 teachers at SD Muhammadiyah PK Kottabarat and 18 teachers at SD Muhammadiyah 10 Types. Research data was collected using a questionnaire, then tested for data analysis using SPSS. At SD Muhammadiyah PK Kottabarat it is known that the tcount value is 5.403, ttable is 2.045, and the significance is 0.000. Meanwhile, at SD Muhammadiyah 10 Types, it is known that the tcount value is 2.538, ttable is 2.120, and the significance is 0.02. Based on these results, it can be concluded that at Muhammadiyah PK Kottabarat Elementary School and Muhammadiyah 10 Tipes Elementary School, teacher welfare variables have a significant effect on teacher performance.